The role of the microenvironment in tumor growth and spreading - V. О. Bitsadze; Е. V. Slukhanchuk; А. G. Solopova; J. Kh. Khizroeva; F. E. Yakubova; Е. А. Orudzhova; N. D. Degtyareva; Е. S. Egorova; N. А. Makatsariya; N. V. Samburova; V. N. Serov; L. А. Ashrafyan; et al. (IRBIS LLC, 2024)
Introduction. The tumor microenvironment (TME) consisting of non-tumor cells and other components plays a crucial role in cancer development by promoting uncontrolled tumor growth.Aim: to detail all the components in TME and their contribution to carcinogenesis by analyzing available publications.Results. Currently, TME study is of great interest in the medical field. Its crucial role in the tumor initiation, progression, and spreading is emphasized. Several constituents have been identified in TME including cancer-associated fibroblasts, neutrophils, adipocytes, tumor vasculature, lymphocytes, extracellular matrix, dendritic cells, neutrophil extracellular traps, etc. Thromboinflammatory reactions are also considered an important TME element.Conclusion. TME constituents can serve as new targets for both diagnostics and antitumor therapy.